Anti-Tumoral Effect and Action Mechanism of Exosomes Derived From Toxoplasma gondii-Infected Dendritic Cells in Mice Colorectal Cancer - Zhu, Shilan; Lu, Jinmiao; Lin, Zhibing; Abuzeid, Asmaa M. I.; Chen, Xiaoyu; Zhuang, Tingting; Gong, Haiyan; Mi, Rongsheng; Huang, Yan; Chen, Zhaoguo; Li, Guoqing (Frontiers in Oncology, 2022)
Toxoplasma gondii is an obligate intracellular protozoan with anti-tumor activity against a variety of cancers. However, the therapeutic effect of T. gondii on colorectal cancer is unclear, and using direct Toxoplasma infection in immunotherapy involves safety concerns. This study investigated the anti-tumor effect and mechanism of exosomes derived from dendritic cells (DC) infected with T. gondii (Me49-DC-Exo). We used the density gradient centrifugation to isolate exosomes from uninfected DCs (DC-Exo) and T. gondii Me49-infected DCs (Me49-DC-Exo). The isolated exosomes were identified by transmission electron microscopy, nanoparticle tracking analysis, and western blotting. Me49-DC-Exo significantly inhibited tumor growth and reduced the proportion of M2 macrophages in the blood of tumor-bearing mice. In vitro, Me49-DC-Exo suppressed macrophage (RAW264.7) polarization to M2 phenotype. miRNA sequencing revealed that multiple miRNAs in Me49-DC-Exo were differentially expressed compared with DC-Exo. miR-182-5p, miR-155-5p, miR-125b-2-3p, and miR-155-3p were up-regulated, while miR-9-5p was significantly down-regulated. Transfecting mimics or inhibitors of these differential miRNAs into RAW264.7 cells showed that miR-155-5p promoted M1 macrophage polarization while inhibiting M2 macrophage polarization. Bioinformatics prediction and dual-luciferase reporter assay confirmed the suppressor of cytokine signaling 1 (SOCS1) as a direct target of miR-155-5p. Silencing SOCS1 gene expression in RAW264.7 cells increased CD86 + CD206 - M1 macrophage proportion and inducible nitric oxide synthase and tumor necrosis factor-α mRNA levels. However, arginase1 and transglutaminase 2 expression levels decreased. These results suggest that the exosomes inhibit macrophage polarization to M2 phenotype and regulate SOCS1 expression by delivering functional miR-155-5p. These findings provide new ideas for colorectal cancer immunotherapy.